2005
DOI: 10.1021/es048590e
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Assessment of Modes of Toxic Action of Pharmaceuticals in Aquatic Life

Abstract: An ecotoxicological test battery based on a mode-of-action approach was designed and applied to the hazard identification and classification of modes of action of six pharmaceuticals (carbamazepine, diclofenac, ethinyl estradiol, ibuprofen, propranolol, and sulfamethoxazole). The rationale behind the design of the battery was to cover the relevant interactions that a compound may have with biological targets. It is thus not comprehensive but contains representative examples of each category of mode of toxic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
132
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(138 citation statements)
references
References 60 publications
3
132
0
3
Order By: Relevance
“…Several studies have shown that narcosis is strongly related to the lipophilicity of the compound, commonly expressed as the n-octanol-water partition coefficient (K ow ) (De Voogt et al, 1988). Consequently, deviations from the relationship between effect concentrations and K ow values may indicate a different mode of action (Bearden and Schultz, 1998;Escher et al, 2005). This was clearly demonstrated previously for soil invertebrates chronically exposed to several PACs (Sverdrup et al, 2001;Droge et al, 2006), and therefore in the present study we followed the same approach.…”
Section: Narcosis Versus Specific Effectsmentioning
confidence: 65%
“…Several studies have shown that narcosis is strongly related to the lipophilicity of the compound, commonly expressed as the n-octanol-water partition coefficient (K ow ) (De Voogt et al, 1988). Consequently, deviations from the relationship between effect concentrations and K ow values may indicate a different mode of action (Bearden and Schultz, 1998;Escher et al, 2005). This was clearly demonstrated previously for soil invertebrates chronically exposed to several PACs (Sverdrup et al, 2001;Droge et al, 2006), and therefore in the present study we followed the same approach.…”
Section: Narcosis Versus Specific Effectsmentioning
confidence: 65%
“…Pharmaceuticals do not appear as isolated compounds in river water but as a mixture, and data on the responses of aquatic organisms to a mixture of pharmaceuticals are very limited. Escher et al [36] reported higher toxicity of a pharmaceutical mixture than separated products. Flaherty et al [37] indicated unpredictable and complex effects of a pharmaceutical mixture on Daphnia survival, growth, and reproduction.…”
Section: Relationships Between Chemical and Biological Parametersmentioning
confidence: 99%
“…The question is how to recognize that two chemicals have a common MoA, and therefore can be grouped together? One possibility is to assign MoA based on molecular interactions between the chemical and the biological system which initiate specific toxicity pathways like binding to the estrogen receptors, or measuring specific cellular reactions that are indicative for specific effects such as chlorophyll interference in tests with algae (Hamadeh et al, 2002;Escher et al, 2005;Nendza and Wenzel, 2006;Woods et al, 2007;Pereira-Fernandes et al, 2014). Another approach is the grouping of chemicals on the basis of structural rules (Schüürmann, 1998;Verhaar et al, 2000;Enoch et al, 2008;Blackburn et al, 2011).…”
Section: Introductionmentioning
confidence: 99%